Evaluasi Pelaksanaan Operasi Kepolisian Aman Nusa II Dalam Penanganan Corona Virus Disease-19 Menuju New Normal Kepolisian Resort Ogan Komering Ilir - Ramadhan, Muhammad Rizki; Mudasir, Mudasir; Mardianto, Mardianto (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
Overcoming the Coronavirus or coronavirus through prevention and appeals to people who still do Overcoming the corona virus through prevention and handling of people who still do not follow health guidelines on the streets and in crowded places is the responsibility and mandate of the police regarding efforts to prevent and handle the spread of COVID. a virus -19 Virus. The purpose of this study was to evaluate the implementation of safe Nusa activities in Ogan Komering Ilir Regency. This research is a descriptive research with a qualitative approach. The information used is based on qualitative data. Based on the findings of the investigation into the activities/operations of the Ogan Komering Iliri Aman Nusa II Resort Police as part of the acceleration of response and prevention due to the 2019 Corona Virus (Covid-19) outbreak that occurred in several countries. In some parts of Indonesia, including Ogan Iliri (OKI) Regency, it will be held from 18 April 2020 to 31 May 2020 for 44 (forty four) days safely, correctly and smoothly. However, Aman Nusa II activities/operations can still be said to be safe and appropriate if individual members are not involved in criminal activities during the Covid-19 pandemic. This can be seen from the dimensions of context, input, process, and output.